Pengaruh Konseling Apoteker Terhadap Pengetahuan Pasien Diabetes di Apotek Kf 27 Medan - Ririn Anastasia Butar Butar; Wiryanto M.S; Aminah Dalimunthe (Jurnal Ners, 2025)
Abstract This study aimed to analyze the effect of pharmacist counseling on the knowledge of patients with Type 2 Diabetes Mellitus (T2DM) at Kimia Farma 27 Pharmacy, Medan. The study employed a quasi-experimental design with a one-group pretest-posttest approach. A total of 112 T2DM patients participated, selected through total sampling. Data were collected using a validated questionnaire administered before and after pharmacist counseling. The results showed a significant increase in the average knowledge score from 3.07 ± 1.69 to 7.36 ± 1.70, with a p-value of 0.000. The direct counseling sessions, supported by written educational materials, effectively improved patients’ understanding. These findings highlight the strategic role of pharmacists in enhancing medication literacy in primary healthcare settings. This intervention serves as a strong foundation for developing standardized pharmacy counseling modules in community pharmacies. Keywords: pharmacist counseling, medication literacy, type 2 diabetes mellitus, patient education, community pharmacy.